EL COMPLEJO "GALLINA CIEGA" (COLEOPTERA: MELOLONTHIDAE) EN EL CULTIVO DE MAÍZ, EN EL MADRONAL, MUNICIPIO DE AMATENANGO DEL VALLE, CHIAPAS, MÉXICO - Ramírez Salinas, Concepción; Castro Ramírez, Adriana E. (Instituto de Ecología, A.C., 2000)
In order to develop a basis for sustainable and integrated pest management of white grubs, we identified the species referred as "white grub complex", present in maize cultivation systems. We determined the damage caused by these grubs in relation to the all stages of development of both the agricultural pest and of the associated crop. The research was carried out in the tzeltal Maya community of El Madronal, in the municipality of Ametenango del Valle, Chiapas, México, in nine irrigated agricultural plots and in two non-irrigated plots throughout the agricultural cycle of 1996-1997. In both systems maize is planted annually, principally as a mono-crop. We determined that the intense damage to the plants' roots during the annual cycle ¡s caused by eight species of the Family Melolonthidae. Six of these species are in the genus Phyllophaga and two in the genus Anómala. The species which caused the greatest damage in the irrigated plots was P. menetríesi (this represent the first register in México of this species as an important agricultural pest), and for the non-irrigated plots, P. ravida. We also identified other six species with scarabaeiform larvae, but which do not feed the roots of maize. Of these, five belong to the subfamilies Melolonthinae, Dynastinae and Rutelinae. The last belongs to the Family Scarabaeidae.